Fostering meaningful learning experiences through student engagement - Ktoridou, Despo 1968-; Doukanari, Eli; Eteokleous, Nikleia 1979- (IGI Global, 2021)
"The book presents the latest scholarly information on curriculum development, instructional design, and pedagogical methods fostering student engagement learning initiatives and meant to open new doorways to future research activities regarding both face-to-face and online instructor roles"--
Includes bibliographical references and index. - Description based on title screen (IGI Global, viewed 12/12/2020)
Keywords: Motivation in education; Curriculum planning; Web-based instruction; Design; Critical pedagogy; Critical pedagogy; fast; Curriculum planning; fast; Motivation in education; fast